Associations of long-term cumulative C-reactive protein and glycoprotein acetyls concentrations in childhood, adolescence and adulthood with adulthood retinal microvascular structure - Repo, Oskari; Juonala, Markus; Niinikoski, Harri; Rovio, Suvi; Mykkänen, Juha; Cheung, Carol Y.; Ala-Korpela, Mika; Vaahtoranta-Lehtonen, Hanna; Nevalainen, Jaakko; Jula, Antti; Kähönen, Mika; Lehtimäki, Terho; et al. (Elsevier, 2026)
Backgroung and aims
Inflammation is associated with cardiovascular disease development and microvascular dysfunction. The aim of the present study is to test the hypothesis that long-term exposure to chronic inflammation in childhood and adulthood is associated with adverse retinal microvascular structure in young and mid-adulthood.
Methods
We analyzed data derived from the Special Turku Coronary Risk Factor Intervention Project (STRIP) and longitudinal Cardiovascular Risk in Young Finns Study (YFS). In STRIP, fundus photos were taken in young adulthood (aged 26 years), and in YFS in mid-adulthood (aged 34–49 years). Retinal microvascular measures were derived in both cohorts (arteriolar and venular diameters and tortuosity; additionally, fractal dimensions in STRIP). Cumulative exposure as the area under the curve for high-sensitivity C-reactive protein (hsCRP) and glycoprotein acetyls (GlycA), and other conventional cardiovascular risk factors was determined over a 15- and 17-year period in STRIP, and a 10-year period in YFS. Overall, retinal microvascular and cumulative hsCRP and/or GlycA were available for 344 STRIP and 1211 YFS participants, thus forming the cohort of the present study.
Results
In both cohorts, cumulative hsCRP was associated with wider venules when adjusted for sex (and age in YFS), and further for related cardiovascular risk factors. In young adulthood (STRIP), higher exposure to cumulative hsCRP was associated with decreased venular tortuosity, whereas in mid-adulthood (YFS), the association was inverse. Cumulative hsCRP was not associated with arteriolar measures whereas cumulative GlycA showed no significant association with any retinal microvascular measures.
Conclusions
Long-term cumulative hsCRP exposure was associated with wider venules in young and mid-adulthood, whereas the associations with venular tortuosity were inconsistent. Wider retinal venules might act as a marker for cumulative inflammatory burden.